Toxicity of cryoprotectants to Chlorococcum dissectum microalgae cells - Vozovyk, Krystyna; Chernobai, Nadiia; Kadnikova, Nataliya; Rozanov, Leonid (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):304